The Effect Of Corporate Governance on Company Value - Aruw Widya Mawarni; Fajar Gustiawaty Dewi; Fitra Dharma (Jurnal Ekonomi Manajemen Bisnis dan Akuntansi, 2024)
This article aims to describe the importance of good corporate governance in a company. This research method uses qualitative research methods with a literature review approach. The research data source is in the form of articles related to Good Corporate Governance. The results of the literature review show that good corporate governance that is implemented well will be able to influence the company's financial performance and the value of the company in the eyes of investors. Good Corporate Governance exists to direct companies to be better at managing the company. Good company management can influence company value and also company performance. With increasing company performance and company value, investors believe that the company can fulfill the obligations of its shareholders. That way, investors will have the confidence to invest their capital in the company. With many investors who believe in investing their capital in the company, the company's operational activities will also be better.